ORGANIZATIONAL CITIZENSHIP BEHAVIOUR THAT MEDIATED THOSE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE TOWARDS EMPLOYEE PERFORMANCE AT XYZ ORGANIZATION - Rahmawaty, Aprilian; Johanes Lo, Singmin (Dinasti Publisher, 2021)
Main purpose of this research was to explored An organizational citizenship behaviour's influenced that mediate the impact from transformational leadership and organizational culture towards employee performance at XYZ organizational. Research population was all employees from XYZ Organization, amounting to 113 employees. Sample method by non-probability sampling with saturated sampling as sampling technique so respondents chosen was 113 respondents. Data analysis method in this research used Structural Equation Model (SEM) with assist of Smart PLS version 3.2.9 program. These result indicated that transformational leadership and organizational culture has a positive and significant influence on employee performance Likewise to organizational citizenship behaviour.